Some Evidence on the Relationship between Performance-Related Pay and the Shape of the Experience--Earnings Profile. - Brown, Sarah; Sessions, John G. (Southern Economic Journal, 2006)
We investigate the relationship between performance-related pay (PRP) and the shape of workers' experience-earnings profiles. In particular, we argue that the slope of the profile depends critically upon the degree of 'equity' held by workers in their enterprise as measured by the extent of PRP. The implication is that the slope of the profile for PRP workers falls between those of their zero-equity fixed-wage, and one hundred per cent equity self-employed, counterparts. Our empirical analysis of three British data sets, namely the British Social Attitudes Survey, the British Household Panel Survey, and the British Family Expenditure Survey, supports this prior.